Experimental histochrome's effect on the renal excretory function - O. S. Talalayeva; A. Yu. Zharikov; S. A. Fedoreyev; Ya. F. Zverev; V. M. Bryukhanov; N. P. Mishchenko; V. V. Lampatov (Бюллетень сибирской медицины)
The aim of present investigation was to establish possible histochrome's effect on the renal excretory function. During 10 days was being administrated histochrome by subcutaneous injections in dose 10 mg/kg. Every 2 days was being detected daily renal excretions of water, creatinin, sodium and potassium. Long-term histochrome's administration was followed by a fivefold increasing of water excretion and comparable amplification of creatinin. Sodium's and potassium's excretions were increasing to a lesser degree. The revealed histochrome's diuretic effect qualitatively reminds action of diuretic plants, but quantitatively it was compared with thiazid's one.